2013
DOI: 10.1186/1472-6882-13-281
|View full text |Cite
|
Sign up to set email alerts
|

Possible modulation of FAS and PTP-1B signaling in ameliorative potential of Bombax ceiba against high fat diet induced obesity

Abstract: BackgroundBombax ceiba Linn., commonly called as Semal, is used in various gastro-intestinal disturbances. It contains Lupeol which inhibits PTP-1B, adipogenesis, TG synthesis and accumulation of lipids in adipocytes and adipokines whereas the flavonoids isolated from B. ceiba has FAS inhibitory activity. The present study was aimed to investigate ameliorative potential of Bombax ceiba to experimental obesity in Wistar rats, and its possible mechanism of action.MethodsMale Wistar albino rats weighing 180-220 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Balasubramanian et al [2] demonstrated that GF (18 mg/kg/day) orally for 30 days significantly reduce HFD induced gain in BW of rats. Also, Gupta et al [29] showed that GF deceased BW and LI in male Wistar rats fed HFD for 10 weeks which received GF (50 mg/kg/day) in the last 3 weeks of the experiment. This effect may be due to the prevention of pathological mechanisms responsible for excessive fat accumulation, dyslipidemia and weight gain, possibly by increasing leptin sensitivity, providing anorexic effect, and increasing energy expenditure.…”
Section: Parameters Groupsmentioning
confidence: 97%
“…Balasubramanian et al [2] demonstrated that GF (18 mg/kg/day) orally for 30 days significantly reduce HFD induced gain in BW of rats. Also, Gupta et al [29] showed that GF deceased BW and LI in male Wistar rats fed HFD for 10 weeks which received GF (50 mg/kg/day) in the last 3 weeks of the experiment. This effect may be due to the prevention of pathological mechanisms responsible for excessive fat accumulation, dyslipidemia and weight gain, possibly by increasing leptin sensitivity, providing anorexic effect, and increasing energy expenditure.…”
Section: Parameters Groupsmentioning
confidence: 97%
“…Stem bark of the plant is reported to contain lupeol, β-sitosterol, shamimicin [ 21 ], ceibanephthaquinone, silamiln-A and silamalin-B [ 22 ], magniferin, epicatechin-3-O-b-xylopyra-noside, epicatechin-7-O-b-xylopyranosid [ 23 ], shamiminol, stigmasta-3,5-diene, lupenone and opuntiol [ 24 ]. The plant is reported as anti-inflammatory, anti-oxidant, anti-obesity, hepatoprotective, hypoglycemic and hypotensive activities [ 25 , 26 ]. B. ceiba is used for inflammatory diseases such as asthma, diabetes, wounded glandular swelling [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Phytochemical compositions of methanol extract of the Egyptian B. ceiba flowers indicate the presence of alkaloids, flavonoids, glycosides, saponine, polyphenols, tannins, proteins, carbohydrates, lipids, amino acids and coumarins [33,34]. These valuable compounds offer the potent antioxidant and hypolipedimic properties of BCE in the liver tissues [35]. In our study, we examined the efficacy of these constituents in curing the alcohol addiction that were accompanied by fat intake in comparison to the effect of the standard drug; Fluvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…This explains that the extract may be preventing the pathological mechanisms susceptive for excessive fat accumulation and weight gain due to the presence of bioactive components like alkaloids and glycosides. In addition, the extract is possibly increasing leptin sensitivity, providing anorexic effect and increasing energy expenditure [35,37]. The liver is the primary organ responsible for ethanol metabolism and it is susceptible to alcohol's toxic effects.…”
Section: Discussionmentioning
confidence: 99%